Videre analyser af funktion til modellering af vejtrængsel i trafikmodeller - Berthelsen, Daniel; Laursen, Jacob Falkenberg (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
The assignment involves estimation of parameters for the congestion function (BPR-function) used in the National Traffic Model to describe the relationship between the traffic volume and the speed. Based on collected data, the ???? (alpha) and ???? (beta) parameters of the BPR-function are estimated, after which the National Traffic Model is used to calculate the effect of the estimated parameters. The collected data contains observations from Mastra and observations from Hastrid. In addition to calculations where the estimated parameters are used, sensitivity calculations are also made, in which four scenarios have been set up to examine the significance of the alpha and beta parameters for the calculations in the National Traffic Model. To estimate the alpha and beta parameters, the collected data is processed from Mastra and Hastrid, where it is compared to become wiser on which data makes the most sense to continue to work with in this project. Various analyzes of the Mastra data that is used in this project are made from 20 different selected road count stations in Denmark. The analyzes provides an overview of the traffic situation at the different sites, and based on the data processed, the alpha and beta parameters are estimated by having the parameters of the BPR-function to follow the traffic flow. By adjusting the capacity, it’s possible to make the function fit even better for the data. This project also contains analyses where vehicle data have been joined together to weather data. The analyses contains linear regressions to investigate the effect of the speed for different weather types including a new parameter estimation based on the earlier used method to compare the different estimated alpha and beta parameters to figure out if there’s any difference in the parameter estimations across the different weather types. The last analysis compares the effect of single vehicle data where the data have been aggregated into different intervals, to investigate the effect of vehicle data collected in intervals of 5, 10, 15, 30 and 60 minutes. The results from the model calculations are compared to the observations from the 20 selected data collection stations, showing if it’s possible to make an improved description of congestion, in relation to the current parameters used in the National Road Model.